Relationship of Bird Diversity and Plant Composition Inside The Area Campus Green Space of Universitas Padjadjaran Jatinangor, Sumedang West Java - Deden Nurjaman; Teguh Husodo; Erri Noviar Megantara; Herri Y. Hadikusumah; Indri Wulandari (Biosaintifika: Journal of Biology & Biology Education, 2018)
Padjadjaran University (UNPAD) Jatinangor is currently conducting green Campus program. To support the program, a study of biota living in it, as one of the benchmarks of good or bad environmental conditions, is needed. The green space of Jatinangor Campus is divided into two clusters namely Cluster I green space (Campus Forest) and green space Cluster II (Campus Non Forest). The objective of the research was to know the relationship between diversity of birds with diversity of plants in the green space of Cluster I (Campus Forest) and Cluster II (Campus Non Forest) UNPAD Campus Jatinangor as one of the parameters of successful development of green Campus. This research is descriptive-explorative with census method on bird species and plant composition from green spaces of Cluster I (Campus Forest) and Cluste II (Campus Non Forest) Campus UNPAD Jatinangor. From the observations in Cluster I, we identified 46 species of birds and 77 species of plants, whereas in Cluster II, we identified 32 species of birds and 74 types of plants. The number of bird species is directly proportional to the number of plant species from Cluster I and Cluster II green spaces. From this study it was concluded that the diversity of tree species supports the diversity of bird species.